Toxicity of two drugs towards the marine filter feeder Mytilus spp, using biochemical and shell integrity parameters. (15th January 2022) - Daniel, David; Campos, João C.; Costa, Paulo C.; Nunes, Bruno
Abstract: The increasing presence of anthropogenic contaminants in the environment may constitute a challenge to non-target biota, considering that most contaminants can exert deleterious effects. Salicylic acid (SA) is a non-steroid anti-inflammatory drug (NSAID) which exerts its activity by inhibiting the enzyme cyclooxygenase (COX). Another class of drugs is that of the diuretics, in which acetazolamide (ACZ) is included. This pharmaceutical acts by inhibiting carbonic anhydrase (CA), a key enzyme in acid-base homeostasis, regulation of pH, being also responsible for the bio-availability of Ca 2+ for shell biomineralization processes. In this work, we evaluated the chronic (28-day) ecotoxicological effects resulting from the exposures to SA and ACZ (alone, and in combination) on individuals of the marine mussel species Mytillus spp., using enzymatic (catalase (CAT), glutathione S-transferases (GSTs), COX and CA), non-enzymatic (lipid peroxidation, TBARS levels) and morphological and physiological (shell hardness, shell index and feeding behaviour) biomarkers. Exposure to ACZ and SA did not cause significant alterations in CAT and GSTs activities, and in TBARS levels. In terms of CA, this enzyme was inhibited by the highest concentration of ACZ in gills of exposed animals, but no effects occurred in the mantle tissue. The activity of COX was not altered after exposure to the single chemicals. However, animals exposed to the mixture of ACZ and SA evidenced a significant inhibition of COX activity. Morphological and physiological processes (namely, feeding, shell index, and shell hardness) were not affected by the here tested pharmaceutical drugs. Considering the general absence of adverse effects, further studies are needed to fully evaluate the effects of these pharmaceutical drugs on alternative biochemical and physiological pathways. Graphical abstract: Image 1 Highlights: The assessment of the effects of ACZ and SA was performed in Mytillus spp. It was observed an increase in CAT activity, by opposing to a decrease in TBARS. Mixtures SA + ACZ exerted effects on enzymatic activities (CA and COX). Physiological parameters were not affected by SA or ACZ.